Психологические аспекты занятия танцем - Волков, К. О. (ХНУРЭ, 2012)
Ballroom dancing has evolved into a highly participated and organized sport. In given work the author wants to consider phycology side of this incredibly alluring art and show up the nature of the relations in couple and what kind they should be, and some other phycology aspects between partners when they study, train or perform on the tournaments.